2015
DOI: 10.3354/meps11321
|View full text |Cite
|
Sign up to set email alerts
|

Rapid monitoring of seagrass biomass using a simple linear modelling approach, in the field and from space

Abstract: Resale or republication not permitted without written consent of the publisherUsing in situ measurements (red triangles), we modelled above-ground biomass in over 20 000 benthic photos (inset) and a time-series of seagrass maps (main image).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2015
2015
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 34 publications
0
11
0
2
Order By: Relevance
“…Our model is therefore trained to predict the areas where seagrass of any species, biomass or cover level, could theoretically occur based on environmental conditions. Developing predictive models of the impact of sediment loads on seagrass which incorporate metrics other than presence vs. absence, such as species [ 51 ], cover [ 52 ], or biomass [ 53 ], are beyond the scope of this study, but are an important area of future research. Water clarity was assumed to be influenced by the distance to open ocean (source of clear water) and river mouths (source of turbid water), as they are likely to influence water clarity [ 54 , 55 ].…”
Section: Methodsmentioning
confidence: 99%
“…Our model is therefore trained to predict the areas where seagrass of any species, biomass or cover level, could theoretically occur based on environmental conditions. Developing predictive models of the impact of sediment loads on seagrass which incorporate metrics other than presence vs. absence, such as species [ 51 ], cover [ 52 ], or biomass [ 53 ], are beyond the scope of this study, but are an important area of future research. Water clarity was assumed to be influenced by the distance to open ocean (source of clear water) and river mouths (source of turbid water), as they are likely to influence water clarity [ 54 , 55 ].…”
Section: Methodsmentioning
confidence: 99%
“…The previous section described categorical mapping approaches, however some studies have demonstrated quantitative mapping of a continuous benthic parameter such as live coral cover [92], seagrass standing crop [93] or seagrass biomass [94,95]. In these examples the analysis was based on the correlation between image bands (or combinations of bands) and field data on the parameter of interest.…”
Section: Quantitative Benthic Mappingmentioning
confidence: 99%
“…Sebagai tahap awal untuk mengestimasi karbon tersimpan menggunakan citra satelit, diperlukan model hubungan antara tutupan jenis lamun dengan karbon tersimpannya. Lyons et al (2015), sudah mulai menggunakan pendekatan model linear untuk menganalisis hubungan antara penutupan dan biomassa lamun, namun belum sampai mengestimasi simpanan karbonnya. Oleh karena itu penelitian ini dilakukan untuk mendapatkan model hubungan antara simpanan karbon dengan persen penutupan pada 6 jenis lamun.…”
Section: Pendahuluanunclassified